2008
DOI: 10.1242/jcs.024943
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of axonal regeneration by in vitro conditioning and its inhibition by cyclopentenone prostaglandins

Abstract: Axonal regeneration is enhanced by the prior `conditioning' of peripheral nerve lesions. Here we show that Xenopus dorsal root ganglia (DRG) with attached peripheral nerves (PN-DRG) can be conditioned in vitro, thereafter showing enhanced neurotrophin-induced axonal growth similar to preparations conditioned by axotomy in vivo. Actinomycin D inhibits axonal outgrowth from freshly dissected PN-DRG, but not from conditioned preparations. Synthesis of mRNAs that encode proteins necessary for axonal elongation mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…This system has been of interest because adult sensory neuron axonal regeneration is enhanced by prior 'conditioning' lesions, which activate and inactivate the expression of groups of proteins linked to embryonic regeneration [7,19-21]. Figure 1 shows an example of the outgrowth of unconditioned neonatal and adult sensory neurons.…”
Section: Resultsmentioning
confidence: 99%
“…This system has been of interest because adult sensory neuron axonal regeneration is enhanced by prior 'conditioning' lesions, which activate and inactivate the expression of groups of proteins linked to embryonic regeneration [7,19-21]. Figure 1 shows an example of the outgrowth of unconditioned neonatal and adult sensory neurons.…”
Section: Resultsmentioning
confidence: 99%
“…This effect could be the consequence of a higher effect in axonal integrity produced by Trx1. In this regard, previous studies have linked Trx1 to a strong protection against axonal damage in a model of retinal nerve damage [74, 75], as well as to the regulation of axonal regeneration [76]. The excess of Trx1 in the system could thus contribute to lower the basal levels of pNF-H by tipping the balance toward axonal regeneration rather than disruption.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that 17β-estradiol increased the expression of Trx1 through the cGMP and protein kinase G signaling pathway in neuronal cells (Lee et al, 2003). In addition, Trx1 synthesis may be involved in axonal regeneration, and its inhibition is associated with reduced neurite outgrowth of dorsal root ganglia neurons (Tonge et al, 2008). Both Trx1 and Trx2 may participate in axonal protection.…”
Section: Axonal Protectionmentioning
confidence: 99%